If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2x = 95 Reorder the terms: 2x + 3y = 95 Solving 2x + 3y = 95 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y = 95 + -3y Combine like terms: 3y + -3y = 0 2x + 0 = 95 + -3y 2x = 95 + -3y Divide each side by '2'. x = 47.5 + -1.5y Simplifying x = 47.5 + -1.5y
| 2c+4b=24 | | 5(5b)=25-8b | | 5q+7=-8 | | ((3-(5/2x))/((5/2x)-7)) | | 6b^2=-6+4b | | 7x-1.8=1.7 | | 9y-4y+4=31 | | 5+3r=15 | | 23+2v=25 | | -2(4w-5)+6w=4+5(2w-2) | | y=45x+3 | | 3s^3-2s^2-3s+2=0 | | 4v-16=56 | | 21=-3/2(18)-19 | | -2(4y-5)=34 | | 7(8r-2)-8(3r+4)I= | | 3/5a=33 | | .6a-1.6=.2a+.4 | | 9w+18=3(w-8) | | 2x+y=5-5x-2y+-6 | | -26-3x=x+30 | | 5t*t-12t-12=0 | | -5(v+9)=5v+5 | | f(2.4)=2x^2-3x+5 | | 2y/3=3.9 | | solver-15r+3=r-2+7(8-4r) | | 4x-11y+16=0 | | 12p+11q+p-4q-4p= | | -9v+34=6(v+6) | | 5(u-89)=35 | | -3x-(4)=14 | | 4+5=x+9 |